Respons Pakcoy (Brassica rapa) Akibat Teknik Pemupukan Terhadap Karakter Fisiologis dan Hasil Panen - Suri, Alima Maolidea (Universitas Muhammadiyah Kotabumi, 2025)
Proper cultivation techniques will increase Brassica rapa plant production. One alternative to increase Brassica rapa plant production is through fertilization techniques. This experiment aims to obtain the best fertilization technique to improve the physiological characteristics and harvest yield of Brassica rapa plants. This experiment uses a one-factor Complete Randomized Block Design (RCBD) method. The treatment factors used were the dip fertilization technique, the row fertilization technique, the drip fertilization technique, and the spread fertilization technique. The research stages carried out include preparation of planting media, preparation of seeds, planting, fertilizer application, maintenance and harvesting, followed by observation and data analysis. The parameters observed were leaf area, dry weight, leaf area index, net assimilation rate, plant growth rate, yield per plot and marketability. The data that has been collected is then analyzed with an alpha of 5% and if there is a significant difference it is further tested with BNT (Least Significant Difference) at an alpha of 5%. The drip fertilization technique did not have a significant effect on leaf area, dry weight, leaf area index, net assimilation rate and plant growth rate but had an effect on yield per plot and marketability. The best fertilization technique was the drip treatment.